2014
DOI: 10.1007/s13181-013-0375-y
|View full text |Cite
|
Sign up to set email alerts
|

LIPAEMIC Report: Results of Clinical Use of Intravenous Lipid Emulsion in Drug Toxicity Reported to an Online Lipid Registry

Abstract: The use of intravenous lipid emulsion (ILE) as an antidote has prompted significant academic and clinical interest. Between August 2009 and August 2012, data from cases of ILE use in intoxicated patients in different hospitals on different continents were voluntarily entered into a registry based on the world wide web (www.lipidregistry.org). Here, we report data from this project. Participating centers were given access to the registry following institutional subscription. Specifically sought were details of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 33 publications
0
56
0
2
Order By: Relevance
“…Unlike previously published human case reports, we enrolled consecutive patients that received ILE therapy and our results included patients that survived or died after the administration of ILE. The majority of published case reports on the utility of ILE in this setting have positive outcomes, [22][23][24][25][26][27][28][29][30][31][32] although negative case reports on the effect of ILE in overdose patients have also been published. 54,55 Limitations Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike previously published human case reports, we enrolled consecutive patients that received ILE therapy and our results included patients that survived or died after the administration of ILE. The majority of published case reports on the utility of ILE in this setting have positive outcomes, [22][23][24][25][26][27][28][29][30][31][32] although negative case reports on the effect of ILE in overdose patients have also been published. 54,55 Limitations Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21] To date, the human data on the effectiveness of ILE for cardiovascular toxins has been limited to small case series and reports, and review articles. [22][23][24][25][26][27][28][29][30][31][32] A recently published systematic review on the use of ILE in nonlocal anesthetic overdoses found current evidence to be heterogeneous and low quality. 33 Moreover, several publications have demonstrated adverse effects with its use, including interference with laboratory investigations such as the complete blood count (CBC) and electrolytes.…”
Section: Importancementioning
confidence: 99%
“…Thus far, there are relatively few reports of adverse effects due to ILE. Adverse effects reported in human patients treated using ILE include bronchospasm, elevated serum amylase in the absence of clinical pancreatitis, and transient erythema secondary to extravascular administration [5,16]. However, <1 % of human patients given lipid emulsions as a part of parenteral nutrition develop fat overload syndrome, which can induce lipemia, fat emboli, hepatomegaly, icterus, hemolysis, increased coagulation times, splenomegaly, thrombocytopenia, leukopenia, and pancreatitis [4,12].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid emulsion should not be reused after opening to avoid microbial contamination [9,12,18]. Additionally, lipemia secondary to ILE can interfere with laboratory analyses, including glucose analyzers [4,16]. It is possible that ILE can interfere with lipophilic drugs used therapeutically [5,9].…”
Section: Discussionmentioning
confidence: 99%
“…The LIPAEMIC investigators reported 48 cases of use of ILE where details of intoxicant, treatment and outcome were entered into an online registry [19]. Complete capture of all cases treated in contributing centers was unlikely based on declining reporting rates over the time of data collection, meaning that inherent positive publication bias in case reports and series may still have been acting on this dataset.…”
Section: Case Seriesmentioning
confidence: 99%